The Effect of Work Discipline and Teacher’s Motivation on Teacher’s Performance - Ibrahim, Ibrahim; Fitria, Happy; Puspita, Yenny (Yayasan Sembilan Pemuda Indonesia, 2020)
This paper answered the effect of work discipline and teacher’s motivation partially and simultaneously on teacher’s performance at State Junior High Schools in Babat Toman Musi Banyuasin District. The design of this research is associative research. The number of samples of this study was 100 teachers. The statistical analysis technique used is multiple linear regression analysis. The results showed that there was a significant relationship between work discipline (X1) and teacher’s motivation (X2) on teacher’s performance (Y). This paper concludes that teacher’s work discipline and teacher’s motivation have a positive and significant effect on teacher’s performance. This study recommends that teacher’s work discipline needs to be maintained and teacher’s motivation needs to be considered. It is important to be stimulated so that teacher’s motivation is within each teacher and it is necessary to improve facilities and infrastructure to support teacher’s performance.